Conceptualizing a Model for the Effect of Information Culture on Electronic Commerce Adoption - Herzallah, Fadi A. T.; Al-Sharafi, Mohammed A.; Alajmi, Qasim; Muriati, Mukhtar; Ruzaini, Abdullah Arshah; Eleyan, Dirar (Springer, 2018)
There are many vital roles and attributes played by the internal organizational environment in IT adoption. Technological innovations are adopted as a result of the reaction of many organizations to change and for influencing the business environment. For this study, a conceptual model was developed to focus on the effect of information culture as internal organizational factors on Electronic Commerce (EC) adoption on small and medium enterprises (SMEs). The proposed model buttressed by four of information culture as internal organizational factors. Specifically, the model constructed from, the information integrity, formality, control and proactiveness variables, evaluated their effects and determined how they can optimally be combined to permit EC adoption by SMEs. To achieve the objectives of the research, a pilot study was conducted with 35 managers of ICT SMEs from Palestine, to assess the proposed model. The proposed model will be assisting SMEs managers better understand and increase predictive capacity on EC adoption. This model will be applied to increase the rate at which EC is adopted among SMEs.